Heat treatment optimization of the gas atomized Ti/B-SS powders. (22nd March 2019) - Zhou, Xue; Liu, Ying; Li, Jun; Li, Cheng; Ma, Lingcheng; Fu, Daogui
Abstract: Reticular structure in borated stainless steel (B-SS) ingot can be broken by adding Ti. However, it still display low tensile and impact properties due to the existence of the large size grains. Recently, powder metallurgy showed promising potential for overcoming above mentioned disadvantage. In this paper, titanium-containing borated stainless steel (Ti/B-SS) powders were first prepared by gas atomization. Though the powders showed small grain size, the reticular structure can't be completely eliminated while residual high temperature ferrite phase was also retained in powders. Besides, the micro-hardness of powders was also relatively high, which was not conducive to powder deformation. Thus, a further heat treatment process was added to optimize the powders. The results showed the process of heat treatment can improve the microstructure of the powders. Especially, after the heat treatment of 1100 °C for 5 h, the reticular structure was eliminated and the residual ferrite was reduced. At the same time, TiB2 precipitated evenly. Moreover, owing to the elimination of innerstress and defects, the micro-hardness of the powders showed a sharp decrease from 343.8 HV to 199.4 HV, which provided high quality powders for further powder metallurgy process.